The Concept of Human Ability (Qudratul Insan) in Islamic Education Process - Dadan Nurulhaq (International Journal of Nusantara Islam, 2020)
This study aims to examine the concept of human ability (Qufratul Insan) in the process of Islamic education. The approach used is qualitative, namely research on the condition of natural objects, where researchers as a key instrument. The data collection technique is done by triangulation (combined), data analysis is inductive, and the results of the study emphasize the meaning rather than generalization. The results of the discussion showed that the human potential given by Allah SWT in the form of vision, hearing, and heart that all three have a relationship where hearing functions to maintain knowledge that has been found from the results of learning and learning, vision functions to develop knowledge and add research results by conducting further studies. The heart is in charge of cleansing knowledge of all bad qualities.)